Form-based versus meaning-based in the history of translation from English to Vietnamese through case studies = So sánh phương pháp dịch hình thức và dịch ý nghĩa trong lịch sử dịch thuật Anh – Việt thông qua nghiên cứu trường hợp - Nguyễn, Thị Hồng Anh (2020)
This paper presents a descriptive case study into the manifestations of form-based and meaning-based translation in the history of English – Vietnamese translation in Vietnam with an aim to document the changes in English – Vietnamese translation and the Vietnamese language along the history. Four cases of translation that were produced in four phases in the history of English – Vietnamese translation were selected for analysis. In each case, the manifestations of form-based and meaning-based translation method were documented and presented, from which it was expected that there is at least one pattern of development in the use of form-based and meaning-based methods. The findings show that in each case, the choice of two methods is evident through lexical aspects (word class, words with various senses of meaning), grammatical aspect (passive structures) and textual aspect (text organization). Overall there is a tendency that throughout the time, translation is more meaning-based and the competence of translators also improves. It is recommended that more studies on similar themes but different cases would contribute to justifying the pattern introduced in this project. Studies on the same cases yet different translation aspects would also be insightful.